Agroforestry as Rehabilitation Strategy System in Orang Kayo Hitam Peat Swamp Park Forest, Jambi - Indonesia. Issue 1 (1st February 2023) - Wulandari, C; Iswandaru, D; Novriyanti, N
Abstract: Tropical peat forest ecosystems are unique and have multiple social, economic, and ecological benefits. Factors such as excessive drainage and frequent fires cause peatland degradation. Rehabilitation of deforested and drained tropical peat swamp forests is globally relevant in the context of deforestation and forest degradation. One management system that can be implemented in these conditions combines crops and forest plants (agroforestry). The challenges of the agroforestry application strategy in forest parks are the status of the land, which is a conservation area, and the characteristics of the surrounding community and field conditions. Based on these conditions, it is necessary to conduct this research to support the Orang Kayo Hitam (OKH) forest park development strategy appropriately. The research was conducted in May – June 2021 and used Force Field Analysis based on the opinions of 231 respondents. Based on the research results, it is known that respondents stated that the highest internal driving force is motivation to improve family's economic from agroforestry products (score 52) and the external one is availability of endemic plants (score 45). The respondent's opinion about the highest internal inhibiting factor is related to public knowledge of benefits from endemic plant species (score 39), while for external is related to market networks for Non Timber Forest Products (NTFP) market (score 43).